Challenges and Possibilities of Implementing Deep Learning Approach in English Language Learning at Junior High School - Dhea Ayu Astuti Olii; Soleman Bouti; Irmawaty Umar (Universitas Islam Negeri Palopo, 2026)
This study examines the challenges and possibilities of implementing a Deep Learning approach in English language learning at MTs Al Islah Gorontalo. Using a qualitative case study involving observations, interviews with three English teachers, and analysis of lesson plan documents, the study identified that implementation is in a transitional stage. Possible outcomes include teachers' established initial understanding of the Deep Learning concept. Furthermore, classroom observations revealed high student participation, cognitive engagement (questioning and discussion), and enthusiasm, indicating the successful creation of a conducive and meaningful learning environment. Challenges include the acknowledged difficulty in designing truly meaningful and differentiated tasks for students. Structural barriers also emerged, with heavy administrative workloads consuming teachers' time, limiting the space needed for deep learning innovation and creative instructional design. The study concludes that despite these pedagogical and structural barriers, the Deep Learning approach holds significant potential for transformative English language education.